Malaysia from PSPTN perspective using data envelopment analysis - Wan Husain , Wan Rohaida (2014)
Objective of the study is to look at the efficiency of Malaysia in terms of its effectiveness in achieving the national policies on higher education as stipulated by a blueprint called Pelan Strategik Pengajian Tinggi Negara (PSPTN or National Higher Education Strategic Plan, NHESP). Accordingly, 9 variables have been selected in such a way that they capture important issues addressed by the 5 pillars of PSPTN namely Research & Innovation; Enculturation of Lifelong Learning; Improving the Quality of Teaching & Learning; Intensifying Internationalization; and Widening Access and Increasing Equity. 43 countries have been analysed and short listed based on availability of data on the chosen variables. Malaysia is identified as 92.6% efficient using variable return to scale DEA model. It is above the average performance of 90.23%. Among the 24 countries that are identified as fully efficient, only Indonesia, Bulgaria and Slovenia are identified as efficient peers for Malaysia with significant weights. Discussion focuses on the practice of efficient countries.